2004
DOI: 10.2320/matertrans.45.2960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Grain Orientation on Evolution of Deformed Microstructure in Hot Compressed Ni-30Fe Alloy

Abstract: An experimental procedure has been developed to investigate systematically the effect of initial grain orientation on the evolution of deformed microstructure in Ni-30Fe alloy. The investigation of identical grains before and after hot deformation made it possible to trace the evolution of microstructure deformed up to 50% at a strain rate of 1/s in a single pass at 1023 K using a hot compression simulator. The localized inhomogeneous shear bands occurred in almost all grains. On the other hand, the near f110g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Cho et al reported greater advances in high angle boundaries and the subdivision of grains under the deformation with shear strain those under that without shear strain using Ni-30Fe alloy (face-centered cubic). 10) They observed microstructure was affected by the shear strain, but the texture change was not examined. Kang et al reported on the quantitative relationship between texture and misorientation, according to two deformation modes of plane strain compression and simple shear using IF steel (body-centered cubic; BCC).…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al reported greater advances in high angle boundaries and the subdivision of grains under the deformation with shear strain those under that without shear strain using Ni-30Fe alloy (face-centered cubic). 10) They observed microstructure was affected by the shear strain, but the texture change was not examined. Kang et al reported on the quantitative relationship between texture and misorientation, according to two deformation modes of plane strain compression and simple shear using IF steel (body-centered cubic; BCC).…”
Section: Introductionmentioning
confidence: 99%
“…If the orientation of the grain boundary is not parallel to the shear surface, it can reduce the size of the pits on the processed surface. Cho et al (2004) studied the effect of initial crystallographic orientation on the microstructure evolution of Ni-30 Fe alloy and found that the development of the deformed microstructure will be affected to a certain extent by the initial grains. Wu et al (2015) found through copper microcutting experiments that the grain orientation has a great influence on the cutting force and the formation of burrs.…”
Section: Introductionmentioning
confidence: 99%
“…The UFGM whose grain size is less than 1 lm is induced by warm-or cold-rolling process under severe plastic deformation (Cho et al, 2004;Kim et al, 2005). A refinement of microstructures of a metal caused by dislocation behaviors is closely connected with a macroscopic deformation.…”
Section: Introductionmentioning
confidence: 99%